2004
DOI: 10.1023/b:mcbi.0000044386.45054.70
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer of CuZn superoxide dismutase enhances the synthesis of vascular endothelial growth factor

Abstract: Nitric oxide (NO) and reactive oxygen species (ROS) are emerging as important regulators of angiogenesis. NO enhances VEGF synthesis in several cell types and is required for execution of VEGF angiogenic effect in endothelial cells. Similarly, hydrogen peroxide induces VEGF synthesis and recent studies indicate the involvement of ROS in signaling downstream of VEGF stimulation. VEGF synthesis can not only be enhanced by gene transfer of VEGF but also by overexpression of NO synthase genes. Here, we examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 81 publications
2
21
0
Order By: Relevance
“…4). Thus, although Cu/ZnSOD and MnSOD have been considered as antioxidant enzymes in cytosol and mitochondria, respectively, they seem to serve as H 2 O 2 -generating, angiogenic enzymes in some settings [113]. These studies indicate that SOD treatment becomes anti-angiogenic and angiogenic depending on its isoform or location.…”
Section: Effects Of Superoxide Dismutase (Sod) On Angiogenesismentioning
confidence: 97%
See 1 more Smart Citation
“…4). Thus, although Cu/ZnSOD and MnSOD have been considered as antioxidant enzymes in cytosol and mitochondria, respectively, they seem to serve as H 2 O 2 -generating, angiogenic enzymes in some settings [113]. These studies indicate that SOD treatment becomes anti-angiogenic and angiogenic depending on its isoform or location.…”
Section: Effects Of Superoxide Dismutase (Sod) On Angiogenesismentioning
confidence: 97%
“…By contrast, FGFinduced angiogenesis and tumor development are enhanced in Cu/ZnSOD transgenic mice [112] and gene transfer of Cu/ZnSOD in NIH3T3 fibroblasts enhances VEGF synthesis through an increase in H 2 O 2 [113]. Connor et al [114] have reported that overexpression of MnSOD promotes mitochondrial H 2 O 2 production, thereby stimulating EC sprouting and neovascularization in the CAM assay.…”
Section: Effects Of Superoxide Dismutase (Sod) On Angiogenesismentioning
confidence: 99%
“…The expression of VEGF is regulated by HRE and the Sp1 responsive (Grzenkowicz-Wydra et al, 2004). It seems that the regulation of VEGF expression by either HRE or the Sp1 responsive element is copper-dependent, so that without HIF-1␣ accumulation, which acts through HRE, copper stimulates VEGF expression by affecting Sp1 regulation.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Consistent with SOD3 2/2 mice, SOD1-deficient mice show impaired neovascularization, as assessed by reduction of blood flow recovery and capillary density in ischemic muscle (80). Overexpression of human SOD1 in mouse NIH 3T3 fibroblasts increased SOD activity, enhanced intracellular generation of H 2 O 2 , and significantly stimulated VEGF production (81). FGF-induced angiogenesis and tumor development are enhanced in SOD1 transgenic mice (150).…”
mentioning
confidence: 93%